Faktor Penghambat Keterpilihan Calon Legislatif Perempuan: Studi Pemilu Legislatif Tahun 2014 di Kabupaten Aceh Besar - Muhammad Taufiq (Universitas Sumatera Utara, 2018)
Women and men have equal position in politics. Women are frequently facing discrimination in politics. Policy of affirmative action requiring 30% of women in legislative listed candidates is apparently not coherent with their position in parliament. There are several considered factors against women to be elected in legislative. This study is focusing on analysis of several factors against women election in legislative within Aceh Besar District between2014-2019. This study will be conducted by using descriptive qualitative research, through interview, documentation and literature study. There are four factors to be discussed are 1). strong patriarchy in religious and cultural system within the community., 2). Lack of women economical support to participate in general election. 3). internal factor of women themselves. 4). Shortage of media support to disseminate or socialize women candidates.